Cavernous sinus syndrome secondary to intracranial lymphoma in a cat. Issue 6 (June 2014) - Guevar, Julien; Gutierrez-Quintana, Rodrigo; Peplinski, George; Helm, Jenny R; Penderis, Jacques
Cavernous sinus syndrome is characterised by internal and external ophthalmoplegia and sensory deficits over the head due to combined deficits of the three cranial nerves (CNs) responsible for the eye movements and pupil function (CN III, IV, VI) and at least one branch of the trigeminal nerve (CN V). It has rarely been described in cats and may occur secondarily to inflammatory, infectious or neoplastic lesions within the region of the cavernous sinus on the ventral aspect of the calvarium. This report describes the clinical and magnetic resonance imaging findings in a 14-year-old domestic shorthair cat with neurological deficits compatible with cavernous sinus syndrome caused by presumptive extranodal lymphoma. Treatment with chemotherapy resulted in clinical and imaging remission. Identification of the neurological deficits in cavernous sinus syndrome allows accurate neuroanatomical localisation in order to target diagnostic imaging studies.